Tether or Stepping Stone? The Relationship between Perceived External Reputation and Collective Voluntary Turnover Rates - Makarius, Erin; Stevens, Charles; Tenhiälä, Aino (Sage Journals, 2017)
Signaling theory suggests that resources such as firm reputation can send multiple signals that create dual pressures on stakeholders. These tensions are apparent when examining the relationship between a firm’s reputation and the collective voluntary turnover rates it experiences. On the one hand, a favorable reputation may tether employees to the firm due to the perceived desirability of working for a reputable company, resulting in lower voluntary turnover rates. On the other hand, a favorable reputation may make employees believe they are more marketable and thus may serve as a stepping stone relating to higher voluntary turnover rates. The purpose of this study is to investigate whether and when reputation acts as a signal of desirability or a signal of ease of movement in predicting collective voluntary turnover rates. We find some evidence for an overall tethering effect for more reputable firms. In addition, our findings demonstrate that reputation is more likely to result in stepping stone effects in certain signaling environments including when firms are in more munificent industries, are younger, and have higher pay levels. Tethering effects are observed when firms are in less munificent industries, are older, and have lower pay levels.
Keywords: Reputation; Turnover; Collective voluntary turnover; Signaling theory; 53 Ciencias Económicas::5311 Organización y dirección de empresas; ODS 8 - Trabajo decente y crecimiento económico